Perancangan Sistem Informasi Invetaris Barang Berbasis Web Di PT. Paramata Baraya International Mengunakan Metode RAD - Difa Madani (UNIVERSITAS STEKOM, 2025)
This study is dedicated to the design and implementation of a web-based inventory management platform for PT. Paramata Baraya International. replacing the manual Excel system that is ineffective and susceptible to mistakes. The Rapid Application Development (RAD) method is chosen for its quick and iterative approach to software development. The system is built using the Next.js framework and PostgreSQL as the database, with Prisma ORM for database management. Key features include item management, real-time status tracking, calibration, maintenance, equipment rental, and automatic notifications. The implementation results show a 60% increase in item search efficiency, 95% data accuracy, and an 80% reduction in manual input errors. This study is significant as a solution for companies engaged in calibration and maintenance of measuring instruments.